Thermodynamic Evidence of Fermionic Behavior in the Vicinity of One-Ninth Plateau in a Kagome Antiferromagnet - Guoxin Zheng; Dechen Zhang; Yuan Zhu; Kuan-Wen Chen; Aaron Chan; Kaila Jenkins; Byungmin Kang; Zhenyuan Zeng; Aini Xu; D. Ratkovski; Joanna Blawat; Alimamy F. Bangura; et al. (Physical Review X)
The spin-1/2 kagome Heisenberg antiferromagnets are believed to host exotic quantum entangled states. Recently, the reports of 1/9 magnetization plateau and magnetic oscillations in a kagome antiferromagnet YCu_{3}(OH)_{6}Br_{2}[Br_{x}(OH)_{1-x}] (YCOB) have made this material a promising candidate for experimentally realizing quantum spin liquid states. Here, we present measurements of the specific heat C_{p} in YCOB in high magnetic fields (up to 41.5 T) down to 0.46 K, and the 1/9 plateau feature has been confirmed. Moreover, the temperature dependence of C_{p}/T in the vicinity of 1/9 plateau region can be fitted by a linear in T term which indicates the presence of a Dirac spectrum, together with a constant term, which indicates a finite density of states contributed by other spinon Fermi surfaces. Surprisingly, the constant term is highly anisotropic in the direction of the magnetic field. Additionally, we observe a double-peak feature near 30 T above the 1/9 plateau which is another hallmark of fermionic excitations in the specific heat. This combination of gapless behavior and the double-peak structure strongly suggests that the 1/9 plateau in YCOB is nontrivial and hosts fermionic quasiparticles.